Epidemiological profile of elderly people hospitalized for femur fractures in the state of Paraná from 2017 to 2023 (Research, Society and Development, 2024)
Objective: to identify the epidemiological profile of elderly people hospitalized for femur fractures in the state of Paraná from 2017 to 2023, the mortality rate, the average hospitalization rate and incidence according to sex and age group. Methods: this was a retrospective, descriptive study with qualitative and quantitative analysis based on data collected from the Department of Information Technology of the Brazilian Unified Health System (DATASUS), in which filters were selected representing the study variables related to the period from January 2017 to December 2023 in the state of Paraná. Conclusion: 69.7% of hospitalizations of elderly people due to femur fractures were female. However, the mortality rate was higher in men. In addition, it was a condition that proved to be costly for public health, resulting in an annual average of 14.9 million reais.